2007
DOI: 10.1186/1472-6920-7-44
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer awareness of undergraduate medical and dental students

Abstract: BackgroundThe incidence of oral cancer is increasing in the United Kingdom. Early detection of oral cancers makes them more amenable to treatment and allows the greatest chance of cure. Delay in presentation and/or referral has a significant effect on the associated morbidity and mortality. Lack of general medical practitioner and general dental practitioner oral cancer knowledge has been shown to contribute to delays in referral and treatment. The aim of this study was to investigate the oral cancer awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

35
127
4
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(180 citation statements)
references
References 31 publications
35
127
4
14
Order By: Relevance
“…Several studies have reported the oral cancer awareness of dental students (Jaber et al, 1997;Carter and Ogden, 2007;Ogden and Mahboobi, 2011). On the other hand, the effectiveness of tobacco use cessation (TUC) counseling in dental office and the fact that the performance of these programs can be as effective in dental practice as in other primary health care settings are well documented (Warnakulasuriya, 2002;Carr and Ebbert, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the oral cancer awareness of dental students (Jaber et al, 1997;Carter and Ogden, 2007;Ogden and Mahboobi, 2011). On the other hand, the effectiveness of tobacco use cessation (TUC) counseling in dental office and the fact that the performance of these programs can be as effective in dental practice as in other primary health care settings are well documented (Warnakulasuriya, 2002;Carr and Ebbert, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…10,16,17 There is a general lack of knowledge about oral cancer among the UK population 18,19 and even among some medical and dental professionals. 2 While it would appear that tobacco usage is widely recognised by patients as a risk factor for OSCC, the effect of alcohol is not. 4,19 A previous study identified that significant numbers of patients attending the dental access centre in Nottingham (Integrated Dental Unit, IDU, Nottingham) have lifestyle habits that make them vulnerable to oral cancer, and that dental access centres might be wellplaced to play a role in the prevention of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…2 The disease is largely preventable by avoiding known risk factors. 2,4,5 The main risk factors are smoking Objective In the United Kingdom in 2006, 5,325 persons were diagnosed with oral cancer; and in 2007 it caused around 1,850 deaths. The purpose of this study was to assess the patient awareness, in a dental access centre, of a poster and leaflet campaign providing information about smoking and excess alcohol consumption as risk factors in the development of oral cancer, and to explore dental patients' beliefs and perceptions about these risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations